A novel fusion transcription factor drives high cellulase and xylanase production on glucose in Trichoderma reesei. (February 2023) - Lv, Dongmei; Zhang, Weixin; Meng, Xiangfeng; Liu, Weifeng
Graphical abstract: Highlights: The DBD of Xyr1 and the TAD of Tmac1 were fused to construct XT. XT enabled improved (hemi)cellulase production on glucose in Trichoderma reesei . XT elevated the abundance of hemicellulases in the secretome. The produced enzyme cocktail improved the saccharification of pretreated corn stover. Abstract: To reduce the high cost of (hemi)cellulase production in lignocellulose biorefining, it is important to develop strategies to enhance enzyme productivity from economic and also readily manipulatable carbon sources. In this study, an artificial transcription factor XT was designed by fusing the DNA binding domain of Xyr1 to the transactivation domain of Tmac1. When overexpressed in Trichoderma reesei QM9414 Δ xyr1, the XT recombinant strain (OEXT) greatly improved (hemi)cellulase production on repressing glucose compared with QM9414 on Avicel with 1.7- and 8.2-fold increases in pNPCase and xylanase activity, respectively. Both activities were even higher (0.9- and 33.8-fold higher, respectively) than the recombinant strain similarly overexpressing Xyr1. The dramatically enhanced xylanase activities in OEXT resulted from the elevated expression of various hemicellulases in the secretome. Moreover, the enzyme cocktail from OEXT improved the saccharification efficiency toward corn stover by 60% compared with enzymes from QM9414 with equal volume loading.